Effects of Knowledge and Value on Quality of Supportive Peer Feedback. Issue 3 (May 2021) - Tornwall, Joni; Xie, Kui; Yu, Shirley L.; Stein, David; Zurmehly, Joyce; Nichols, Robert
Abstract : Background: Motivational barriers and lack of knowledge about peer review inhibit creation of supportive peer feedback between nursing students. Purpose: The purpose of this study was to examine the effects of knowledge of peer-review practices and value for the process of creating supportive peer feedback on the quality of feedback nursing students create for their peers. Method: Data from 155 graduate nursing students were analyzed in this quasi-experimental, repeated-measures design, using analysis of covariance and conditional process analysis. Results: Students who had high levels of knowledge and a strong sense of value for providing feedback to peers produced higher-quality supportive peer feedback. Conclusion: Even when a student has sufficient knowledge and skills to produce supportive peer feedback, their ability may not transfer to real peer-review contexts if they do not also have a strong sense of value for providing high-quality feedback to peers. Abstract : Supplemental digital content is available in the text.